The Republic of Seychelles Systematic Country Diagnostic - World Bank (Washington, DC, 2017)
The Seychelles Systematic Country Diagnostic (SCD) aims to identify the most pressing constraints to inclusive, sustained growth in Seychelles, based on a comprehensive search for, and analysis of, evidence. The SCD is presented using a slide deck which lays out the analysis and results. This document provides a brief overview of the approach taken, and sets the stage for the SCD. It also provides additional information: six selected supplementary topical notes, and annexes (data diagnostic, summary of consultations, and sources). The framework adopted by the SCD takes as its starting point that Seychelles is a successful, high-income, small island state. The country now seeks to secure the sustainability of its development progress to date, to accelerate this progress, and to address a high level of public concern being reflected in political discourse over disparities in incomes and opportunities. The SCD examines Seychelles’ economic growth characteristics, the characteristics of poverty and income distribution (inclusion), and the risks to environmental, social and macroeconomic sustainability. The approach is systematic in that it attempts to be as comprehensive as possible, within the constraints of the available data, by harnessing the existing evidence and conducting new analysis where feasible, informed by consultations. Finally, the SCD sorts the 13 constraints identified into five top priorities, five additional priorities, and a further three areas which should be considered for priority action, subject to confirmation from additional analysis (‘likely priorities’). This prioritization was based on an assessment of how important each constraint was, directly, to meeting the relevant challenge, indirectly, through its potential impact in helping to loosen other constraints (complementarity), the strength of the evidence base on the importance of the constraint, and, finally, the attainability of addressing the constraint (reflecting factors such as cost, technical difficulty and timeframe).